2013
DOI: 10.1088/1475-7516/2013/12/014
|View full text |Cite
|
Sign up to set email alerts
|

Testing the dipole modulation model in CMBR

Abstract: Abstract. The hemispherical power asymmetry, observed in the CMBR data, has generally been interpreted in terms of the dipole modulation model for the temperature fluctuations. Here we point out that this model leads to several predictions, which can be directly tested in the current data. We suggest tests of the hemispherical power asymmetry both in real and multipole space. We find a significant signal of the dipole modulation model in WMAP and PLANCK data with our tests. The dipole amplitude and direction a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 28 publications
(92 reference statements)
2
37
0
Order By: Relevance
“…We have extended the results obtained in a recent paper [53], which showed that the dipole modulation model leads to correlations among spherical harmonic multipoles, a lm and a * l ′ m ′ with m ′ = m and l ′ = l + 1. In that paper we defined a statistic, S H , which provides a measure of this correlation in a chosen multipole range.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…We have extended the results obtained in a recent paper [53], which showed that the dipole modulation model leads to correlations among spherical harmonic multipoles, a lm and a * l ′ m ′ with m ′ = m and l ′ = l + 1. In that paper we defined a statistic, S H , which provides a measure of this correlation in a chosen multipole range.…”
Section: Discussionsupporting
confidence: 72%
“…Hence in this case we generate a foreground residual free full sky CMB data map at this high resolution. Subsequently we downgrade this map to a lower resolution with N side = 32 after applying appropriate Gaussian beam to smooth the mask boundary [53]. This procedure eliminates any breaks that might be introduced at the boundary due to the random filling procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations